ANTIBIOTICS: CONCEPTS, DOSAGE FORMS AND QUALITY ASSESSMENT (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2025)
Antibiotics represent one of the most significant therapeutic advances in modern medicine, revolutionizing the treatment of bacterial infections. This thesis examines the fundamental concepts of antibiotics, explores various pharmaceutical dosage forms used for antibiotic delivery, and discusses comprehensive quality assessment methods.